Pollution and ecological risk assessment, and source identification of heavy metals in sediment from the Beibu Gulf, South China Sea. (July 2021) - Lin, Haiying; Lan, Wenlu; Feng, Qinge; Zhu, Xuetao; Li, Tianshen; Zhang, Ronghai; Song, Hainong; Zhu, Yifan; Zhao, Bohan
Abstract: The Beibu Gulf is an important passageway between China and the Association of Southeast Asian Nations, where there has been an increase in pollution of heavy metals (HMs). High concentrations of Pb, Cr, Cd, Cu, Zn, As, and Hg in surface sediment were found in Qinzhou Bay, Fangchenggang, and other coastal areas. Stochastic geo-accumulation analyses identified the pollution to be "uncontaminated"; however, it had an 18% probability of deterioration. The Cd, Hg, and As pollution were relatively serious. Principal component analysis, positive matrix factor model, and mercury isotopes demonstrated that the HMs could mainly be attributed to industrial sources including petrochemical, coal-fired, metal and metalloid processing, leather tanning, and human activities: anthropogenic sources accounted for approximately 70% of all the contaminations. This study demonstrates the contribution of terrigenous input to HMs even at a low level and provides basic data for the coordinated development of land and marine resources. Highlights: Anthropogenic sources tracing with PMF contributed to 70% of metal content. Hg isotope signature indicated Hg was partly came from industries and municipal. The sediment was at an "uncontaminated" level, had 18% probability of deterioration. The geochemical baseline was consistent with the local background. The spatial distribution suggested the vital impact of land pollution.